Implementation of Social Value Inculcation in Building Fifth Graders' Characters At Primary School Through Social Study Learning - Hidayat, Dharma Try Kusuma; Raharjo, Tri Joko; Haryati Setyaningsih, Nas (Educational Management, 2021)
This research discusses the social value inculcation implementation in building the fifth graders' characters at primary schools through social study learning. Living together in a society requires a particular value as a reference to interact with other people. This value is called as a social value. The family has a role in fostering human based on social value. Social value inculcation at school covers practical aspects. However, unfortunately, learning at schools mostly emphasizes the cognitive aspect. The objectives of this research were: 1) finding out the social value inculcation implementation in Social study learning for fifth graders of primary schools. 2) finding out the inhibiting factors and solution experienced by the teachers in instilling social values through social study learning for fifth graders of primary school. 3) finding out the outcomes of social value inculcation implementation in building the fifth graders' characters of primary school through social study. This research applies a qualitative descriptive method. Qualitative study is a study to understand a particular experienced phenomenon by research subjects, such as behaviours, perceptions, motivation, actions, and so on holistically by describing them into words and languages. It is done in a specific scientific context by using various scientific methods. The findings showed (1) the teachers' attitudes toward the fifth graders of Public Primary School 1 Terban and Public Primary School 6 Terban were innovative. Their attitudes reflected social study learning; (2) the inhibiting matters during the learning were from the teachers, learning materials, and learning media. The attempts to overcome the hindrances were providing training for social study teachers that was not their field of expertise; (3) the teachers were successful in instilling social-affective values based on the given indicators. The research implication showed excellent social-affective inculcation for the students through social study. Teachers were successful in instilling social-affective values based on the given indicators. Honesty, Politeness, Discipline, Tolerance, and Cooperative